Student acceptance of the usage of padlet in guiding research statistics analysis / Dr. Nurul Hidayana Mohd Noor and Hasnatulsyakhira Abdullah Hadi - Mohd Noor, Nurul Hidayana; Abdullah Hadi, Hasnatulsyakhira (Universiti Teknologi MARA, Kedah, 2024)
Padlet is a free e-learning application best described as an online whiteboard. Using this application in teaching and learning is one alternative to improve students’ achievement and performance. This study aims to identify the factors that influence the impact of student acceptance of Padlet application in the learning research statistics analysis for the completion of their final year project. This study relied on the Unified Theory of Acceptance and Use of Technology (UTAUT). Based on UTAUT, the study has identified five main determinants that could influence student acceptance: the instructor’s effectiveness, the student’s competency with technology, the design and content of courses, accessibility of essential resources, and infrastructure dependability. This study used a cross-sectional survey, and data were collected from 185 students from the Faculty of Administrative Science and Policy Studies, UiTM. Overall, the research findings show the instructor’s effectiveness, student’s competency with technology, design and content of courses, accessibility of essential resources, and infrastructure dependability significantly influence the acceptance of the Padlet application. The instructor’s effectiveness is the most significant predictor. This study implies that educators are advisable to employ teaching methods that are more fun, productive, and effective compared to traditional methods.